And I'll scratch yours [compact disc] - Gabriel, Peter, 1950- (Universal Music Australia, 2013)
The original concept was that And I'll Scratch Yours would serve as a companion piece to Gabriel's 2010 covers album Scratch My Back. The idea was to give the artists whose songs Gabriel covered on Scratch My Back a medium to reciprocate? And I'll Scratch Yours would feature those artists covering Gabriel's songs. However, several of the artists ultimately declined to record covers of Gabriel's material. The release version of the album deviated from its initial concept in having two new artists (Feist and Joseph Arthur) contributing covers to the album.